2017
DOI: 10.4014/jmb.1705.05008
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic SMRT Sequencing-Based Exploration of Novel Lignocellulose-Degrading Capability in Wood Detritus from Torreya nucifera in Bija Forest on Jeju Island

Abstract: Lignocellulose, composed mostly of cellulose, hemicellulose, and lignin generated through secondary growth of woody plant, is considered as promising resources for biofuel. In order to use lignocellulose as a biofuel, biodegradation besides high-cost chemical treatments were applied, but knowledge on the decomposition of lignocellulose occurring in a natural environment is insufficient. We analyzed the 16S rRNA gene and metagenome to understand how the lignocellulose is decomposed naturally in decayed Torreya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Active enzymes related to the breakdown of carbohydrates are classified into six groups: glycoside hydrolase (GH), glycosyl transferase (GT), auxiliary activity (AA), carbohydrate esterase (CE), polysaccharide lyases (PL), and carbohydrate-binding domains (CBM). The cooperation of multiple CAZymes in lignocellulose degradation was studied in microbial consortia originating from compost [ 4 ], woodlice gut [ 9 ], forest [ 10 ], and biogas-producing digesters [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active enzymes related to the breakdown of carbohydrates are classified into six groups: glycoside hydrolase (GH), glycosyl transferase (GT), auxiliary activity (AA), carbohydrate esterase (CE), polysaccharide lyases (PL), and carbohydrate-binding domains (CBM). The cooperation of multiple CAZymes in lignocellulose degradation was studied in microbial consortia originating from compost [ 4 ], woodlice gut [ 9 ], forest [ 10 ], and biogas-producing digesters [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phylum Actinobacteria was the most abundant bacteria phylum identified and followed by Proteobacteria. The phyla, Actinobacteria, and Proteobacteria, were also found in tree decayed process [32]. Zhou et al.…”
Section: Resultsmentioning
confidence: 99%
“…The phylum Actinobacteria was the most abundant bacteria phylum identified and followed by Proteobacteria. The phyla, Actinobacteria, and Proteobacteria, were also found in tree decayed process [32]. Zhou et al reported that Firmicutes, Actinobacteria and Proteobacteria were the dominant phyla in rice straw composing with pig manure [9].…”
Section: Dynamics Of Bacterial Community Composition During Compostingmentioning
confidence: 99%
“…This is in accordance with prior findings in decaying wood of pine (Kielak et al ., 2016 ), beech (Valásková et al ., 2009 ), and in microcosms containing beech sawdust inoculated with Phanerochaete chrysosporium (Hervé et al ., 2014 , 2016 ). It has also been reported that Xanthomonadaceae were able to degrade the lignocellulose (cellulose, hemicellulose and lignin) of different lignocellulose substrates under controlled conditions (Zimmermann, 1990 ; Behera et al ., 2014 ; Ceballos et al ., 2017 ; Oh et al ., 2017 ). At genus level, the isolated bacterial community was composed primarily of Pseudomonas , which aligns with previous results demonstrating this genus as the most abundant in many organs as well as sap of grapevine (West et al ., 2010 ; Martins et al ., 2012 , 2013 ; Faist et al ., 2016 ; Deyett et al ., 2017 ; Compant et al ., 2019 ; Deyett and Rolshausen, 2019 ).…”
Section: Discussionmentioning
confidence: 99%